Componential Analysis of Headgear in English - Haira Rizka (Universitas Sanata Dharma, 2018)
This research aims to: (1) classify the hyponym of headgears in English based on their dimensions, (2) examine meaning relations of hyponym and superordinate, and (3) investigate the meaning relations of each co-hyponym. This research employs componential analysis of Kreidler (1998) to examine hyponym components of headgears in English. This is a descriptive qualitative research which describes componential analysis of headgears in English. The data were collected through observation and note taking technique. The collected data were then analyzed by employing textual analysis method. The findings reveal that: (1) 24 hyponyms of headgear are classified into 4 dimensions: wearer, shape, material, and function, and they expose the shared and differentiating features of each hyponym; (2) meaning relation of superordinate can substitute its hyponym, while hyponym cannot substitute its superordinate because the characteristics or features of a hyponym do not include all characteristics or features of a superordinate; (3) meaning relation of co-hyponym is not substitutable because each lexeme (hyponym) has differentiating features and semantic meaning. It is concluded that by employing componential analysis, similar lexemes show their differences.Keywords: componential analysis, headgears, hyponym, superordinate